Investigation on Shear Lugs Used in Equipment Foundations of Nuclear Engineering - Yuan Gong; Xinbo Li; Chen Zhao; Yanhua Zhao (Buildings, 2025)
This paper investigates the shear performance of shear lugs commonly used in nuclear equipment foundations. A total of six groups of H-shaped steel shear lug specimens, six groups of angle steel shear lug specimens, and eight groups of steel plate shear lug specimens are designed and tested under horizontal shear loading. The failure modes, shear capacities, and deformation characteristics of the specimens are systematically examined. Furthermore, the influence of the embedment depth of the shear lug and the distance from the shear lug to the concrete edge on the shear performance of specimens is thoroughly analyzed. Based on the test results, equations for calculating the shear capacity of shear lugs are proposed. The result indicates that the failure modes of the three types of specimens under shear loading mainly show concrete shear breakout failure, and the changes in the embedment depth and concrete edge distance have a large effect on the shear capacity and ductility of the specimen. The proposed equations show good agreement with the test results, which can provide a theoretical foundation for the design of the shear lugs used in nuclear engineering.